Acetylation and phosphorylation of SRSF2 control cell fate decision in response to cisplatin - Edmond, Valerie; Moysan, Elodie; Khochbin, Saadi; Matthias, Patrick; Brambilla, Christian; Brambilla, Elisabeth; Gazzeri, Sylvie; Eymin, Beatrice (The EMBO journal, 2011)
SRSF2 is a serine/arginine‐rich protein belonging to the family of SR proteins that are crucial regulators of constitutive and alternative pre‐mRNA splicing. Although it is well known that phosphorylation inside RS domain controls activity of SR proteins, other post‐translational modifications regulating SRSF2 functions have not been described to date. In this study, we provide the first evidence that the acetyltransferase Tip60 acetylates SRSF2 on its lysine 52 residue inside the RNA recognition motif, and promotes its proteasomal degradation. We also demonstrate that the deacetylase HDAC6 counters this acetylation and acts as a positive regulator of SRSF2 protein level. In addition, we show that Tip60 downregulates SRSF2 phosphorylation by inhibiting the nuclear translocation of both SRPK1 and SRPK2 kinases. Finally, we demonstrate that this acetylation/phosphorylation signalling network controls SRSF2 accumulation as well as caspase‐8 pre‐mRNA splicing in response to cisplatin and determines whether cells undergo apoptosis or G 2 /M cell cycle arrest. Taken together, these results unravel lysine acetylation as a crucial post‐translational modification regulating SRSF2 protein level and activity in response to genotoxic stress. SR family proteins regulate alternative splicing. In this study, the Tip60 acetyltransferase regulates splicing by directly acetylating the splicing factor SRSF2, leading to its proteasomal degradation, and indirectly by relocalising the SRPK1/2 kinase, thereby reducing the phosphorylation levels of SRSF2.